TANTANGAN DAN PELUANG KEBIJAKAN PENDIDIKAN ISLAM DI INDONESIA PADA ABAD 21 - Elman, Moh. (CV. Jendela Gagasan, 2024)
This research aims to explore the direction of Islamic education policies in the 21st century, along with the challenges and opportunities ahead. The study employs a literature review approach, utilizing sources such as books, journals, articles, and relevant written reports. The findings indicate that Islamic education policy in Indonesia in the 21st century is focused on decentralization to grant more autonomy to educational institutions, enhancing curriculum relevance by integrating 21st-century skills like critical thinking and collaboration. The main challenge lies in the centralized system that limits innovation and the development of curricula that meet contemporary needs. However, opportunities lie in leveraging institutional autonomy, technology to enhance learning, and developing modern skills for students.